How are meta-analyses being conducted and reported in dentistry? - Leticia Tainá de Oliveira Lemes; Lara Dotto; Bernardo Antonio Agostini; Gabriel Kalil Rocha Pereira; Rafael Sarkis-Onofre (Universidade Estadual de Campinas, 2021)
Aim: This study aimed to evaluate how meta-analyses are conducted and reported in dentistry. Methods: We conducted a search to identify dentistry-related Systematic Reviews (SRs) indexed in PubMed in 2017 (from January 01 until December 31) and published in the English language. We included only SRs reporting at least one meta-analysis. The study selection followed the 4-phase flow set forth in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement (PRISMA), and it was independently conducted by two researchers. Data extraction was performed by one of three reviewers, and data related to conducting and reporting of the meta-analysis were collected. Descriptive data analysis was performed summarizing frequencies for categorical items or median and interquartile range for continuous data. Results: We included 214 SRs with meta-analyses. Most of the studies reported in the title that a meta-analysis was conducted. We identified three critical flaws in the included studies: Ninety (90) meta-analyses (43.1%) did not specify the primary outcome; most of the meta-analyses reported that a measure of statistical heterogeneity was used to justify the use of a fixed-effect or random-effects meta-analysis model (n=114, 58.5%); and a great part did not assess publication bias (n=106, 49.5%). Conclusion: We identified deficiencies in the reporting and conduct of meta-analysis in dentistry, suggesting that there is room for improvement. Educational approaches are necessary to improve the quality of such analyses and to avoid biased and imprecise results.